2022
DOI: 10.1039/d2cc00979j
|View full text |Cite
|
Sign up to set email alerts
|

Metallation of sensitive fluoroarenes using a potassium TMP-zincate supported by a silyl(bis)amido ligand

Abstract: Combining a bulky bis(amide) and a reactive one-coordinate TMP (2,2,6,6-tetramethylpiperidide) ligand, a new mixed K/Zn heteroleptic base has been developed for regioselective zincation of fluoroarenes. This special ligand set allows...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…[19] For example, using a TMP-based potassium zincate supported by a bulky bis(amide) ligand Ph 2 Si(NAr*) 2 (Ar* = 2,6-diisopropylpheny), we reported zincation of 1 required 3 h at refluxing temperatures in THF or three days at room temperature. [28] The efficient metalation of 1 under mild reaction conditions aligns better with the reactivities previously described using [NaM(HMDS) 3 ] (M = Fe, Co) for the ferration (or cobaltation) of 1. Mechanistic studies for these reactions have revealed that initial NaÀ H exchange takes place followed by trapping of the trisfluorophenyl fragment by the divalent transition metal.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…[19] For example, using a TMP-based potassium zincate supported by a bulky bis(amide) ligand Ph 2 Si(NAr*) 2 (Ar* = 2,6-diisopropylpheny), we reported zincation of 1 required 3 h at refluxing temperatures in THF or three days at room temperature. [28] The efficient metalation of 1 under mild reaction conditions aligns better with the reactivities previously described using [NaM(HMDS) 3 ] (M = Fe, Co) for the ferration (or cobaltation) of 1. Mechanistic studies for these reactions have revealed that initial NaÀ H exchange takes place followed by trapping of the trisfluorophenyl fragment by the divalent transition metal.…”
Section: Resultssupporting
confidence: 77%
“…[42][43][44] Significantly less activated substrates such as fluorobenzene and 1-fluoronaphthalene are also quantitatively zincated in 24 h at room temperature to give products 2 d and 2 e. This is striking as previous approaches using alternative zincating reagents mentioned above fail to metalate these substrates in reasonable yields even when harsh reaction conditions are employed. [28,45] Bromo and chloro para-substituted arenes are zincated easily in 1 h to give zincates 2 f and 2 g. Ortho, meta, and para fluorotoluene can be regioselectively zincated ortho to the fluorine substituent to give products 2 h-2 j avoiding any competing lateral metalation of the methyl substituent as reported for 2-fluorotoluene using the aforementioned LiNK superbase, which favors the benzylic metalation product. [7] Reactivity studies with 2-and 4-fluoroanisole revealed that acidifying effects take prevalence over coordination effects, thus favoring quantitative zincation at the ortho-position to the F substituent furnishing 2 k and 2 l (Figure 3).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A very similar deprotonative complexation was utilized by Hevia et al in the syntheses of potassium amido metalates of Zn, Mg, and Mn. [26,28] A third synthesis attempt involving trans-amination of the homoleptic triamido ferrate K(Et 2 O) 2 [Fe(hmds) 3 ] (3) with the rac Ph LH 2 showed no conversion by 1 H NMR despite a closely literature precedent. [29,30] Crystalline rac-1 was isolated as THFmonosolvate (by EA; Mp 176 °C, decomp.…”
Section: Resultsmentioning
confidence: 99%
“…In this case the bulky ligand was proposed to be key, providing steric protection for the trapping of the C 6 F 4 dianion, although forcing reaction conditions were required (16 h, 70 °C). 9 Sodium ferrate [(dioxane)NaFe(HMDS) 3 ] can also promote the di-ferration of activated fluoroarenes, although the scope of this reactivity has not been fully investigated. 5 a Opening new ground in this area, building on the mechanistic understanding acquired in sodium-mediated cobaltations here we evaluate the potential of 1 to promote dimetalations of fluoro- and chloro-arenes.…”
mentioning
confidence: 99%